IMPLEMENTASI TEKNOLOGI SUPLEMENTASI PROBIOTIK KUNYIT BAGI MITRA PEMBUDIDAYA IKAN LELE DI KABUPATEN NAGAN RAYA, ACEH - Saputra, Fazril; Khairi, Ikhsanul; Suryadi, Suryadi; Zulfadhli, Zulfadhli; Nasution, Muhammad Arif; Hendri, Afrizal; Abdan, Mu'amar; Zuriat, Zuriat (Jurnal Abdi Insani, 2025)
The potential for aquaculture in Aceh Province is enormous, one of which is in the Nagan Raya Regency area. Fish farmers in the Nagan Raya Regency area have long cultivated freshwater catfish using a conventional system. This catfish cultivation system does not increase the production of farmed fish and does not produce organic fish. This activity aims to educate and assist in applying turmeric probiotic supplementation technology to increase farmed fish production and produce organic catfish. The implementation of this activity is carried out using education and assistance. The stages of implementing the activity include initial discussion with farmer partners (UPR Clarias Fish Farm), program preparation, education of community service activities, community service activity workshops, monitoring and evaluation, and activity reporting. Indicator of success in the education and assistance method is that partners understand the material and practices presented by the presenter regarding turmeric probiotic supplementation and good fish farming methods. This activity is evaluated through pre-test and post-test questionnaires using the material provided. This community service activity is said to be successful if the average value of the farmer partners is obtained ≥75% of the post-test questionnaire given. The results of this community service activity are in the form of increased knowledge and understanding of farmer partners. The harvest results also showed an increase in mass production of farmed fish given turmeric probiotics compared to farmed fish without turmeric probiotics. In conclusion, UPR Clarias Fish Farm's fish farming partners experienced an 80% increase in understanding of turmeric probiotic supplementation and catfish production using turmeric probiotics increased the length gain by 3.9 cm longer or 17.89% compared to without probiotics and fish given turmeric probiotics were also 25.96 grams heavier or 21.72% heavier than without probiotics.